Steppe Ecosystems in Chilean Patagonia: Distribution, Climate, Biodiversity, and Threats to Their Sustainable Management - Radic Schilling, Sergio Javier; Corti, Paulo; Muñoz Arriagada, Rene Santiago; Butorovic Alvarado, Nicolas Santiago; Sanchez Jardon, Laura (My University, 2023)
Steppe ecosystems in Chilean Patagonia are located in the Andean rain shadow zones in the Aysén and Magallanes administrative regions, on the eastern slopes of the Andes along the border with Argentina, and in the north-central sector of Tierra del Fuego island. This chapter describes the distribution, climatic conditions, biodiversity, and changes in vegetation coverage of the steppe in Chile. Steppe biodiversity faces threats due to the negative impacts of multiple anthropogenic activities, particularly the development of the hydrocarbon sector, grazing pressure, wildfires, and the introduction of exotic species, as well as global climate change. Conservation of the Patagonian steppe in Chile depends both on protection within state parks or reserves and on cultural changes in the management of the unprotected area; economic uses and conservation must be integrated through sustainable management strategies.
Keywords: Steppe